Claims of the Tax Authority against Businesses for Invalidation of Transactions to Exclude VAT and CIT Offcets - Safonova, O.N. (Право и государство, № 3 (108), 2025)
The paper analyzes the claims of the tax authorities of the Republic of Kazakhstan against businesses concerning the invalidation of transactions for the purpose of excluding VAT and CIT offsets. It outlines the legal framework used by the tax authorities to justify their claims, including civil and tax legislation, and explores the most common procedural and evidentiary issues. Particular attention is paid to the role of the Electronic Invoice Information System (ESF IS), which allows tax authorities to monitor and challenge business transactions remotely. The author highlights both the risks posed by such claims to the investment climate and the frequent legal shortcomings in the tax authorities’ arguments. The article also provides practical recommendations and defense strategies for businesses to resist unfounded tax claims, including the collection of documentary evidence, witness testimonies, and a clear legal position. The importance of distinguishing tax law violations from civil law obligations is emphasized. The conclusions contribute to improving legal awareness among businesses and strengthening the protection of taxpayer rights.
Keywords: Tax disputes, transaction invalidation, VAT, CIT, tax control, judicial practice